Amyloid-β and α-Synuclein Immunotherapy: From Experimental Studies to Clinical Trials - Nimmo, Jacqui Taryn; Kelly, Louise; Verma, Ajay; Carare, Roxana O.; Nicoll, James A. R.; Dodart, Jean-Cosme (Frontiers in Neuroscience, 2021)
Alzheimer’s disease and Lewy body diseases are the most common causes of neurodegeneration and dementia. Amyloid-beta (Aβ) and alpha-synuclein (αSyn) are two key proteins involved in the pathogenesis of these neurodegenerative diseases. Immunotherapy aims to reduce the harmful effects of protein accumulation by neutralising toxic species and facilitating their removal. The results of the first immunisation trial against Aβ led to a small percentage of meningoencephalitis cases which revolutionised vaccine design, causing a shift in the field of immunotherapy from active to passive immunisation. While the vast majority of immunotherapies have been developed for Aβ and tested in Alzheimer’s disease, the field has progressed to targeting other proteins including αSyn. Despite showing some remarkable results in animal models, immunotherapies have largely failed final stages of clinical trials to date, with the exception of Aducanumab recently licenced in the US by the FDA. Neuropathological findings translate quite effectively from animal models to human trials, however cognitive and functional outcome measures do not. The apparent lack of translation of experimental studies to clinical trials suggests that we are not obtaining a full representation of the effects of immunotherapies from animal studies. Here we provide a background understanding to the key concepts and challenges involved in therapeutic design. This review further provides a comprehensive comparison between experimental and clinical studies in Aβ and αSyn immunotherapy and aims to determine the possible reasons for the disconnection in their outcomes.